Pola Komunikasi Organisasi Karang Taruna Putra Maulana Mutih Kulon dalam Mempertahankan Solidaritas Anggota - Feny Indah Puspitasari; Dwi Pela Agustina (Calathu: Jurnal Ilmu Komunikasi, 2022)
An organization is formed by several people who have the same goal. Communication is an important basic thing in an organization to achieve a goal. Karang Taruna Putra Maulana, which was formed in 2005, had been on hiatus for five years. So that it can exist and be active again, of course it is built through cohesiveness and a series of communication that exists between members. The problem that will be studied in this research is how the communication pattern of the Karang Taruna Putra Maulana organization in maintaining member solidarity. The purpose of this study is to help an organization interact with each other between its leaders and members or fellow members within the organization by knowing the communication patterns used, so as to maintain member solidarity to align individual goals with the organization in advancing the organization, and minimize future conflicts. This study uses a qualitative type of research that aims to understand complex facts and phenomena that are useful for providing data on communication patterns of youth organizations in maintaining member solidarity. Data collection techniques using the method of observation, interviews, and documentation. After the data is collected, then data analysis is carried out using the theory of motivation. The result of the research is that Karang Taruna Putra Maulana uses all forms of communication patterns, namely wheels, circles, Y, chains and all directions. The pattern that is often used is the Y pattern and all directions. Meanwhile, the pattern that is not effective or rarely used is the chain pattern because the message conveyed is sometimes incomplete. The solidarity of members is built through regular meetings or meetings and informal communication that exists between members. Keywords: organizational communication patterns, youth Organizations, solidarity